2011
DOI: 10.1007/s13165-011-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of dairy products of biodynamic origin is correlated with increased contents of rumenic and trans-vaccenic acid in the breast milk of lactating women

Abstract: Our previous work showed that incorporation of organic dairy products in the maternal diet may lead to increased contents of the conjugated linoleic acid isomers (CLA) in human breast milk, which might positively affect infant's health. Now, the effect of biodynamic-a special form of organic-dairy products in the diet on the CLA content in human breast milk has been analysed. The content of rumenic acid (the main CLA) in breast milk was higher in the women consuming biodynamic products (n =64, 0.323% of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The unpaired t-test results showed significant differences in the content of some fatty acids evaluated: The content of OA (p<0,0001), TVA (p<0,0001), and CLA (p<0,0055) is significantly higher in samples from cohort 2. This is consistent with the previous research findings explain above, that have linked the consumption of organic dairy products to an increase in the levels of these fatty acids in breast milk [30,31].…”
Section: • Cohort 1 Versus Cohortsupporting
confidence: 93%
See 1 more Smart Citation
“…The unpaired t-test results showed significant differences in the content of some fatty acids evaluated: The content of OA (p<0,0001), TVA (p<0,0001), and CLA (p<0,0055) is significantly higher in samples from cohort 2. This is consistent with the previous research findings explain above, that have linked the consumption of organic dairy products to an increase in the levels of these fatty acids in breast milk [30,31].…”
Section: • Cohort 1 Versus Cohortsupporting
confidence: 93%
“…In the milk of these mothers, the contents of CLA and its main precursor TVA increased when transitioning from a conventional diet to a moderately organic and strictly organic one. In the study by Simões-Wüst et al [31], it was also demonstrated that the content of rumenic acid was higher in the breast milk of women who consumed a type of organic dairy product called biodynamic, compared to those consuming conventional or organic dairy products other than biodynamic, which was intermediate. Biodynamic organic farms consider, in addition to organic production guidelines, cosmic rhythms, which they believe result in improvements in plant and livestock production (http://www.demeter.net/).…”
Section: • Cohort 1 Versus Cohortmentioning
confidence: 93%
“…In addition, the incidence of eczema and allergic sensitization of 2‐year‐old infants is lower if mothers consume organic dairy products during pregnancy and breastfeeding, which is associated with rumen FA . Especially in the group that consumes biodynamic milk products, highest contents of CLA and C18:1 t 11 as well as a lower level of C18:1 t 9 are found in breast milk …”
Section: Discussionmentioning
confidence: 99%
“…Today there is a lot of debate about the effects of consumption of dairy products on health. 4 Studies contradict each other depending on the type of dairy product, gender effects or the inclusion of fermented milk products, 56 the region of production, 7 or the origin of dairy products (catchwords: grass milk, organic milk, hay milk, antibiotic-free milk, A2 milk)., 8 , 910 Also the impact of heating was discussed in relation to the health status of French people. 11 Besides the unheated status of fresh milk, also the content of saturated fat, the fatty acid quality and the trans-fats in milk were questioned., 7 , 12 , 13 , 14 The consumption of raw milk or raw milk products has been negatively impacted by zoonotic disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%